Gaya Humor Mahalabiu - Achmad Faisal; Aziza Fitriah (Faculty of Ushuluddin and Humanities, 2020)
Humor has two types; there is a positive humor style, an affiliative and self-enhancing humor style, and a negative humor style. It is an aggressive and self-defeating humor style. Mahalabiu is a type of oral literature that contains a dual meaning (ambiguous), having a speech meaning. Usually, the listener defines another meaning or purpose behind Mahalabiu's humor. This study aims to describe Mahalabiu humor as a Banjarese people culture, whether Mahalabiu is a positive or negative style of humor. This research method is qualitative phenomenologies with data collection techniques using interviews as a significant technique and observations. Based on the results of the interview with Informant in this study, there were three people: the type of interview used is a semi-structured interview—the method of observation as a supporting method for understanding more in-depth information related to Mahalabiu humor. Interviews were conducted with three speakers who knew Mahalabiu Humor; they are one cultural expert in South Kalimantan, 1 Banjar Language expert, and 1 Banjar Language expert who is also a native of Alabi. Based on the research results, Mahalabiu humor style has its humor style, which can be positive and negative depending on who is presenting at the right time. Where Mahalabiu has its characteristics in which Mahalabiu depends on the person who delivered it, and depending on the situation, if the moment is right, then it might be that Mahalabiu becomes humorous affiliative humor and self-enhancing humor. However, if the moment is not right then, Mahalabiu will become aggressive humor and self-defeating humor.